Experimental investigation on the effects of Miller cycle coupled with asynchronous intake valves on the performance of a high compression ratio GDI engine. (15th January 2023) - Qiao, Junhao; Liu, Jingping; Zhang, Quanchang; Liang, Jichao; Wang, Rumin; Zhao, Yangguang; Shen, Dazi
Highlights: The research of asynchronous intake valve Miller cycle with 14.5 geometric compression ratio. A comparative experimental investigation of Otto cycle and AIVMC was conducted. Vortex flow is generated by asynchronous intake valve on the basis of tumble engine. Compared with the baseline engine, the maximum improvement of BSFC is 7.7% with AIVMC. Abstract: In this study, a series of comparative experiments were conducted on a gasoline direct ignition (GDI) turbocharged engine to investigate the effects of asynchronous intake valve Miller cycle (AIVMC) on the performance, combustion and emissions characteristics. The results show that using the asynchronous valve closing in the test engine can not only realize the Miller cycle, but also flexibly control the load, effectively reduce pump loss and improve fuel economy compared to the late intake valve closing. The minimum brake specific fuel consumption (BSFC) of the test engine equipped with and without the AIVMC are 235.59 g/kwh and 255.2 g/kwh at the condition of 2600 rpm and brake mean effective pressure (BMEP) 8 bar, which obtains a reduction of 7.7% compared to the baseline engine. In addition, the corresponding brake thermal efficiency (BTE) of test engine used the AIVMC is 35.6%, which is improved 8.2%. Besides, under the same geometric compression ratio, using the AIVMC in the test engine effectively improves the antiknock performance, keeps the 50% combustion location (CA50) closer to top dead center, shortens combustion duration, and expands the load range of low fuel consumption. As for emission performance, compared with baseline engine, though the application of AIVMC has lower mean in-cylinder temperature, the NOx emissions increases at low and medium loads but decreases at high load while HC emissions increases.